Multisector Growth Models Theory and Application - Roe, Terry L. (Springer New York : Imprint: Springer, 2010)
This book provides a reader with a practical foundation in general equilibrium theory, embeds the theory in a multi-sector dynamic framework, discusses how to practically link the theory to real economic data, and provides clear instructions on how to use existing software – in this case Mathematica – to construct model simulations for policy and other analysis. This book pulls it all together in a conceptually sound, yet practical, manner, and brings the theory to life. A unique feature is the integration of traditional static trade theory into modern neoclassical growth theory so the reader has the sense of building upon known constructs as opposed to learning a sequence of different models. The book provides several examples of real economic problems with policy interests and shows how to "bring these problems to life" with theory and data.